BOOK REVIEW: ELENA PLATON (ED.), "ENCICLOPEDIA IMAGINARIILOR DIN ROMÂNIA II. PATRIMONIU ȘI IMAGINAR LINGVISTIC". GENERAL EDITOR: CORIN BRAGA. IAȘI, POLIROM, 2020, 488 P. - DAMIAN, Catrinel Ioana (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Comprised of twenty studies and spanning over almost 500 pages, the second volume of the Encyclopedia of Romanian Imaginaries (“Enciclopedia imaginariilor din România”) brings forward the idea of imaginative universes born through the usage of language, and proposes to offer readers a comprehensive depiction of the Romanian linguistic imaginary. Along with the other four volumes in the series, which examine the literary, artistic, religious and historical dimensions of the imaginary, this volume focuses on the forms of the written and spoken word, complementing and completing the others with the analysis of the imagery and symbolism generated by speech and discourse.